Morphophysiological approach to heterosis in phosphorus use efficiency in popcorn - Rosimeire Barboza Bispo; Antônio Teixeira do Amaral Junior; Talles de Oliveira Santos; Valter Jário de Lima; Bruna Rohem Simão; Marta Simone Mendonça Freitas; Samuel Henrique Kamphorst; Carolina Macedo Carvalho; Danielle Leal Lamêgo; Flávia Nicácio Viana; Wallace de Paula Bernardo; Eliemar Campostrini; et al. (Cogent Food & Agriculture)
The development of cultivars adapted to phosphorus (P) deficiency is crucial due to the non-renewable nature of this resource. Although heterosis is widely utilized in maize to enhance productivity, studies on the physiological mechanisms of heterosis expression in popcorn maize under P deficiency remain limited, as do investigations of genetic control during the juvenile phase. This study evaluated the genetic control and heterosis effects on growth traits, gas exchange, leaf pigments, chlorophyll fluorescence, and P efficiency in four popcorn maize inbred lines and their hybrids, including reciprocals. Plants were grown in lysimeters under two contrasting P conditions until the V6 stage in a greenhouse. P deficiency reduced most traits, with dominance gene effects predominantly controlling morphophysiological traits and P efficiency under low P. Greater heterosis effects were observed for growth traits like aerial and root dry weight, root P content, and P efficiency under low P. Phosphorus utilization efficiency (PUtE) improved hybrid performance in phosphorus use efficiency (PUE), while higher instantaneous carboxylation efficiency (A/Ci) enhanced net CO2 assimilation rate (A) under P deficiency.